MODERNIZATION OF THE UNDERCARRIAGE OF A VEGETABLE-GROWING TRACTOR TO REDUCE THE MAN-MADE IMPACT ON THE SOIL (Innovative technologies, 2026)
This article presents theoretical studies aimed at reducing soil compaction caused by the tires of four-wheel tractors used in vegetable cultivation and harvesting under the soil and climatic conditions of our republic. The paper describes the structural design and operating principle of improved wheels, as well as methods for determining their traction resistance.In addition, the practical significance of the proposed design solution is analyzed, particularly its contribution to preserving soil fertility, creating favorable conditions for plant root development, and improving the energy efficiency of agricultural machinery. The interaction between the wheels and the soil is modeled under various loads and operating modes, substantiating the reduction in soil compaction and the optimization of traction performance.Furthermore, a comparison between theoretical and experimental results is carried out, highlighting the advantages of the proposed wheel design over conventional tires. Based on the findings, scientific and practical recommendations are developed for the modernization of agricultural machinery and the enhancement of its operational efficiency.
Keywords: wheel; tractor; elastic rod; soil; pneumatic tire; vegetable; improvement; energy saving; compaction